Thoracoscopic microdiscectomy for disc herniation in the thoracic spine: surgical technique and analysis of early results - Juri V. Kivelev; Alexey S. Gaitan; Alexey L. Krivoshapkin (Хирургия позвоночника, 2023)
Objective. To describe the technique and analysis of early results of thoracoscopic microdiscectomy for disc herniation in the thoracic spine. Material and Methods. A retrospective single-center study included 19 patients (15 women and 4 men) who underwent thoracoscopic microdiscectomy in 2018–2020. The median age of patients was 45 years (range 21–75 years); the median time from the onset of symptoms to the first visit to a neurosurgeon was 12 months (range 1–152 months). Before admission to the hospital, all patients complained of pain of varying intensity in the thoracic spine and/or along the lateral surface of the chest. Nine (47 %) patients had sensorimotor neurological deficit in the legs. The outcomes of operations were assessed using the modified MacNub scale, and postoperative complications were classified according to the Clavien – Dindo scale. Early results of treatment were evaluated at the first follow-up examination (on average, 2 months after the intervention). Data analysis was performed using the SPSS statistical program (IBM SPSS Statistics, version 27). Results. The immediate postoperative period was mostly uneventful in 15 (79 %) patients. Four (21 %) Clavien – Dindo grade 1 complications were registered: 1 (5 %) case of purulent discitis, 1 (5 %) pneumonia, 1 (5 %) worsening of sensory disturbances in the leg, and 1 (5 %) deep vein thrombosis of the leg. The average length of hospital stay was three days. Favorable results (excellent, improvement or satisfactory) according to the modified MacNub scale were registered in 16 (84 %) patients in two months after surgery. In three (16 %) cases, the symptoms remained unchanged (unsatisfactory according to the MacNub scale). No deterioration was recorded in any of the cases. Statistical analysis of the data (Fischer’s method, Mann – Whitney U-test) showed that the only prognostic factor affecting the outcome of the operation was the localization of the hernia in the lower thoracic region between the T8 and T12 vertebrae (p = 0.007). Thus, all nine patients with a hernia in the midthoracic region (T4–T8) had a favorable outcome of the operation, in 6 (67 %) of them there were no complaints. In three (30 %) out of 10 patients with a hernia in the lower thoracic region, there was no complete cure. All other factors (gender, age, hernia size, etc.) did not have a statistically significant correlation with the outcome. Conclusion. Thoracoscopic microdiscectomy can be used in the surgical treatment of herniations of the thoracic spine. Additional studies are needed to confirm the effectiveness and safety of the technique in the long term.